Differential effects of genetic vs. environmental quality in Drosophila melanogaster suggest multiple forms of condition dependence. (2nd February 2015) - Bonduriansky, Russell; Mallet, Martin A.; Arbuthnott, Devin; Pawlowsky‐Glahn, Vera; Egozcue, Juan José; Rundle, Howard D.
Abstract: Condition is a central concept in evolutionary ecology, but the roles of genetic and environmental quality in condition‐dependent trait expression remain poorly understood. Theory suggests that condition integrates genetic, epigenetic and somatic factors, and therefore predicts alignment between the phenotypic effects of genetic and environmental quality. To test this key prediction, we manipulated both genetic (mutational) and environmental (dietary) quality in Drosophila melanogaster and examined responses in morphological and chemical (cuticular hydrocarbon, CHC) traits in both sexes. While the phenotypic effects of diet were consistent among genotypes, effects of mutation load varied in magnitude and direction. Average effects of diet and mutation were aligned for most morphological traits, but non‐aligned for the male sexcombs and CHCs in both sexes. Our results suggest the existence of distinct forms of condition dependence, one integrating both genetic and environmental effects and the other purely environmental. We propose a model to account for these observations.